The impact of environmental improvements on the financial performance of leading companies listed in Bursa Malaysia - Ong, Tze San; Teh, Boon Heng; Ang, Yee Woon (International Association of Computer Science and Information Technology, 2014)
This paper analyses the relationship between environmental improvement and the financial performance of firms on a sample of 78 leading companies listed in Bursa Malaysia. This study uses content analysis to verify the extent of information disclosed and reported by companies. The results indicate that efforts to embrace environmental improvement and activities may help firms gain financially.